Pertumbuhan dan Strategi Pengembangan Ekonomi Kreatif Pedagang Angkringan di Pantai Padongko Kabupaten Barru - Ahmadin; La Malihu; Jovita Oktaviani Putri (Research Agency for Humanity and Urban, 2023)
After going through a long stage of development, the economic field has finally arrived at the creative economy level. A condition in which various business opportunities are wide open and creativity is a determining factor in the development of this economic sector. This paper examines the growth and strategies for developing the creative economy through culinary businesses developed by angkringan traders in Padongko Beach, Barru Regency. The results of the study show that the growth of this culinary business is driven by the desire of the government and local communities to create jobs. In its development, the culinary business of the angkringan traders has increased so that it has a significant influence on improving the economy and family welfare. Several business actors who have been in the culinary business for a long time, have high incomes that affect their social life. However, this business experienced setbacks that affected the economic conditions of the traders' families. This creative economy development strategy is studied using SWOT analysis to predict opportunities and challenges in the future.